IDO: USER EVALUATION OF ONLINE FUNDRAISING MOBILE APPLICATION - Chang Zhi Xuan; Sim Ying Jing; Jacky Chen Liam Hin; Yong Suk Qi; Aeni Zuhana Saidin; Sobihatun Nur Abdul Salam, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Many aid organizations have historically relied on conventional methods of fundraising. The technology evaluation has enabled online funding which recently has gained popularity especially during the COVID-19 pandemic. This article's major discussion will focus on the evaluation of iDo, a mobile app for online fundraising. The evaluation processes were thoroughly covered, and the findings demonstrated that this application is usable and effective. This finding indicates that donations made via the internet are accepted, and the features used in this mobile application can serve as a model for other similar applications.